STUDI KELAYAKAN HUTAN LINDUNG MONGGAL SEBAGAI TAMAN WISATA ALAM (TWA) GUNA MENINGKATKAN DAYA TARIK WISATAWAN - Abdurrahman, Abdurrahman; Sutanto, Himawan; Alpian Muhtarom, Zamroni; Mujahid Dakwah, Muhammad; Handayani Rinuastuti, Baiq (Distribusi - Journal of Management and Business, 2023)
The purpose of this research is to analyze the feasibility study of the Monggal protection forest as a nature tourism park (TWA) in order to increase tourist attraction which is expected to be one way to support the growth of Regional Original Revenue (PAD) and the welfare of the local community and drive the local economy. From the general objectives, it can be further elaborated on the specific objectives, namely (1) to analyze the feasibility of non-financial aspects of the TWA business including market, management, social, economic, and cultural aspects, and the environment. (2) to analyze the feasibility of the financial aspects of the TWA business. This research uses quantitative methods with survey techniques with data collection carried out through several stages, namely: Literature study, Observation, and Focus Group Discussion with various stakeholders. The results of this study reveal that the development of TWA in Genggelang Village, Gangga District, North Lombok Regency is feasible to develop due to the consideration that (1) Feasibility from non-financial aspects (2) Feasibility from financial aspects is carried out by calculating the NPV value for 10 years of Rp 1,214,388,386.85 with a rate of return on investment (IRR) of 32%. Then the Net B / C value of Rp 4,043. and Payback Period for 2 years and 3 months